Analysis of Entrepreneurial Potential Among Students at the Faculty of Teacher Training and Education, Pattimura University - Sinay, Francisca Riconita (JENDELA PENGETAHUAN, 2024)
This study explores the strategies for developing tourist attractions in Oma Village, Haruku Island, and Central Maluku, focusing on enhancing the local economy through local tourism development. In a qualitative approach, the study utilized data collection methods, including interviews, observations, and documentation involving key informants such as the village chief, government officials, and residents. Data analysis involved grouping and organizing to identify patterns and categories, which were then translated through SWOT analysis to evaluate the implementation of strategies for developing Air Asol tourism. Findings revealed that the tourism potential of Air Asol holds significant promise if managed effectively. Recommended development strategies include continuous promotion of the Sapta Pesona principles, community-based tourism development, and certification of tourism human resources. The study's conclusion underscores the importance of proper management and suitable strategies to enhance the tourism potential of Oma Village. It is hoped that the research findings will contribute positively to the development of Air Asol tourist attraction and the local economy.